Enabling the detection of UV signal in multimodal nonlinear microscopy with catalogue lens components - Vogel, Martin; Wingert, Axel Wolff; Fink, Rainer; Hagl, Christian Matthias; Ganikhanov, Feruz; Pfeffer, Christian P. (Journal of microscopy, 2015)
Using an optical system made from fused silica catalogue optical components, third-order nonlinear microscopy has been enabled on conventional Ti:sapphire laser-based multiphoton microscopy setups. The optical system is designed using two lens groups with straightforward adaptation to other microscope stands when one of the lens groups is exchanged. Within the theoretical design, the optical system collects and transmits light with wavelengths between the near ultraviolet and the near infrared from an object field of at least 1 mm in diameter within a resulting numerical aperture of up to 0.56. The numerical aperture can be controlled with a variable aperture stop between the two lens groups of the condenser. We demonstrate this new detection capability in third harmonic generation imaging experiments at the harmonic wavelength of ∼300 nm and in multimodal nonlinear optical imaging experiments using third-order sum frequency generation and coherent anti-Stokes Raman scattering microscopy so that the wavelengths of the detected signals range from ∼300 nm to ∼660 nm.